Integrasi Konsep Dasar dan Perencanaan dalam Manajemen Peserta Didik Dilembaga Pendidikan - Eva Athifah; Muhamad Ihsan Khuluki; Beta Hikmah Zahrotunnisa; Dinda Rahmanida; Siswadi Siswadi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study analyzes the urgency of synergy between the conceptual foundations of student management and strategic planning in the educational environment as an effort to optimize the potential of students. This research uses a descriptive qualitative approach through literature study, with secondary data obtained from journal articles, books, and related literature. This study reveals that the success of student management does not only depend on mastery of the theory of educational service principles, but is also largely determined by the accuracy of planning steps, including needs analysis, recruitment, orientation, and student distribution systems. The results of the study show that the alignment between philosophical foundations and systematic managerial procedures is a crucial factor in creating a positive learning ecosystem and supporting the effective achievement of national educational goals. Through this integration, the policies implemented by educational institutions will be more representative in ensuring the comprehensive development of students' interests and talents.